Challenges in conservative management of placenta increta with methotrexate in nulliparous woman - Anitha, A.; Usha, N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Placenta increta is a severe complication of pregnancy normally diagnosed during the second trimester. Early detection could reduce the risk of hemorrhage during abortion or miscarriage; however, guidelines on first‐trimester diagnosis are lacking. We describe a case of placenta increta during the second trimester with retained products of conception and its consequences followed by effective management with methotrexate.